2013
DOI: 10.1007/s10096-013-1878-9
|View full text |Cite
|
Sign up to set email alerts
|

Decreased ciprofloxacin susceptibility in Salmonella Typhi and Paratyphi infections in ill-returned travellers: the impact on clinical outcome and future treatment options

Abstract: The emergence of decreased ciprofloxacin susceptibility (DCS) in Salmonella enterica serovar Typhi and serovar Paratyphi A, B or C limits treatment options. We studied the impact of DCS isolates on the fate of travellers returning with enteric fever and possible alternative treatment options. We evaluated the clinical features, susceptibility data and efficacy of empirical treatment in patients with positive blood cultures of a DCS isolate compared to patients infected with a ciprofloxacin-susceptible (CS) iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 28 publications
2
30
0
1
Order By: Relevance
“…It has been reported that ceftriaxone therapy is associated with a higher rate of treatment failure and relapse than fluoroquinolone therapy, especially in enteric fever (27)(28)(29)(30). However, it has been well established that bacterial isolations susceptible for ciprofloxacin, but showing resistance to nalidixic acid, can lead to poor clinical outcomes and treatment failure (31,32). According to the increasing number of isolated strains of Salmonella with decreased fluoroquinolone-susceptibility, the breakpoints for extraintestinal Salmonella were revised in the CLSI guidelines in 2012 and 2013 (33).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ceftriaxone therapy is associated with a higher rate of treatment failure and relapse than fluoroquinolone therapy, especially in enteric fever (27)(28)(29)(30). However, it has been well established that bacterial isolations susceptible for ciprofloxacin, but showing resistance to nalidixic acid, can lead to poor clinical outcomes and treatment failure (31,32). According to the increasing number of isolated strains of Salmonella with decreased fluoroquinolone-susceptibility, the breakpoints for extraintestinal Salmonella were revised in the CLSI guidelines in 2012 and 2013 (33).…”
Section: Discussionmentioning
confidence: 99%
“…Over time, physicians in areas of endemicity and those treating returning travelers began to report cases of fluoroquinolone failure when treating enteric fever despite the laboratory reporting a susceptible isolate (343,419,(511)(512)(513)(514)(515)(516)(517)(518)(519). It became clear that a subset of strains of Salmonella serovars Typhi and Paratyphi A had emerged that were less susceptible to the fluoroquinolones.…”
Section: Fluoroquinolonesmentioning
confidence: 99%
“…Particular concern for the development of resistance to first-line antimicrobials has arisen in recent decades (5). Decreased ciprofloxacin (CIP) susceptibility has been reported, which has a significant impact on clinical outcomes and future treatment options (6). Furthermore, international travel increases the spread of resistant S. Typhi isolates (6).…”
Section: Introductionmentioning
confidence: 99%